Charting New Frontiers in Islamic Economics and Finance: Innovation, Sustainability, and Inclusive Development - Ibrahim, Azharsyah (Share: Jurnal Ekonomi dan Keuangan Islam, 2025)
This issue brings together innovative research at the nexus of Islamic economic principles and sustainable development. It includes studies of community-based finance and empowerment, such as rotating savings and credit associations, and initiatives in the halal industry that uplift marginalized groups. Other papers examine the digital transformation of Islamic finance, assessing how religiosity and financial literacy influence fintech adoption and exploring investor behavior in Islamic markets. The issue also examines Shariah governance in the context of green banking and corporate sustainability, and analyzes Islamic banks’ efficiency under economic stress; additionally, a systematic review of IFRS adoption in Islamic banking highlights regulatory convergence. Together, these contributions advance theoretical understanding and provide practical guidance for an inclusive, risk-aware, and sustainable Islamic finance sector.